LITERATUR REVIEW: PENGARUH INJEKSI INTRACEREBROVENTRIKULAR STREPTOZOTOCIN PADA OTAK MENCIT SEBAGAI KANDIDAT HEWAN MODEL ALZHEIMER - Daryanti, Edhita Putri; Anggadiredja, Kusnandar; Wibowo, Agung Eru; Santoso, Koekoeh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Background: Animal models of Alzheimer's have now been developed in various studies to become potential animal models suitable for clinical conditions. Alzheimer's in clinical conditions is characterized by Amyloid βeta (Aβ) plaques and intracellular tangles of neurofibrillary tangles as well as disorders of the acetylcholinesterase enzyme in the hippocampus. Rodents used include rats and mice. Mice are used because they are efficient and parts of the brain can be penetrated with a needle without requiring surgery. Objectives: Appropriate toxicant induction is needed so that the process of developing Alzheimer's pathology is known, namely the use of Streptozotocin. Intracerebroventricular induction of strepzotocin in mice needs to be further understood. Material and Methods: The research method uses literature review with identification, screening, evaluation and interpretation of all research results collected through online search engines such as; Sciencedirect, Pubmed, GoogleScholar with keywords and meet the inclusion criteria Results: The results of the synthesis obtained selected data from 8 articles. ICV-STZ has been proven from various studies to induce Alzheimer's pathology in both young and old male mice through neuroinflammatory pathways, oxidative stress, increasing Aβ expression and hyperphosphorylation of Tau as Alzheimer's markers which are similar to clinical patients. Keywords : Alzheimer, Hewan model, Literatur review, Mencit, Streptozotocin.